Pemanfaatan Teknologi Informasi dan Komunikasi (TIK) dalam Pembelajaran Agama Islam Pada Abad 21 - Zahara; Qonita Syam; Eti Hadiati; Sovia Masayu; Ahmad Fauzan (PAI RAFAH, 2024)
The paradigm shift in Islamic Religious Education refers to the learning approach that still applies conventional education. This research aims to find out the challenges of the 21st century for schools in Indonesia. In this article, the author will try to focus the discussion on the problems of Islamic education in Indonesia in the 21st century, challenges, and solutions in responding to the problems of Islamic education. The method used in the preparation of this article is a qualitative method. Then the approach in this research is to use literature studies and references in the form of books, journals, articles, and scientific works. Reflectively, this study wants to review existing ideas, treatments, and/or situations, especially about schools in the 21st century and their challenges. Based on the results of the review, it can be concluded that the challenges faced by schools in Indonesia in the 21st century are such as the mental revolution of teachers, equipping students who are born as digital natives with 21st-century skills, integrating the use of technology in learning, and curriculum reform according to 21st-century tastes.